Getting a Fair Share: Attitudes and Perceptions of Biobank Stakeholders Concerning the Fairness of Sample Sharing. (25th November 2014) - Colledge, Flora; Elger, Bernice
Abstract Biobanks are essential tools for furthering a broad range of medical research areas. However, despite the plethora of national and international laws and guidelines which apply to them, the access and sharing policies of biobanks are only sparsely addressed by regulatory bodies. The 'give and take' process of biosample sharing is largely left up to biobank stakeholders themselves to oversee; it is therefore both in stakeholders' power, and in their interest, to ensure that sample accessibility is fair. This is an important step in motivating researchers to collaborate and pool samples, and is crucial to fostering trust in the absence of universally accepted standard practices. To date, little attention has been paid to how fairness considerations affect scientific material sharing, and no empirical research has been carried out to determine the role that fairness plays in collaborative studies. In order to begin to gain understanding in this area, we interviewed 36 biobank stakeholders currently working in Switzerland, focusing on their perceptions of current and optimal fair sharing practices. Our findings reveal that fairness is an important feature of exchange situations for these stakeholders, and that they have well‐formed notions about the practical elements of fair sample access, although ideas about the concept of fairness itself are vague. In order to support efforts to network biobanks, attention should be paid to this issue to reassure all involved that they are getting a fair share in their cooperative efforts.